Entstehung, Entwicklung und Erfolge des Kompetenznetzes Akute und Chronische Leukämien (KNL) = Leukemia research in Germany : the Competence Network Acuteand Chronic Leukemias - Kossak-Roth, Ute; Saußele, Susanne; Reiter, Andreas; Hehlmann, Rüdiger (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
The Competence Network “Acute and Chronic Leukemias” was founded in 1997 by the consolidation of the leading leukemia study groups in Germany. Key results are the development of new trials and cooperative studies, the setup of patient registries and biobanking facilities, as well as the improvement of study infrastructure. In 2003, the concept of the competence network contributed to the foundation of the European LeukemiaNet (ELN). Synergy with the ELN resulted in cooperation on a European and international level, standardization of diagnostics and treatment, and recommendations for each leukemia and interdisciplinary specialty. The ultimate goal of the network is the cure of leukemia through cooperative research.